Aqua(4-hydroxybenzoato-κO)(4-hydroxybenzoato-κ2O,O′)(1,10-phenanthroline-κ2N,N′)zinc(II) monohydrate - Seik Weng Ng (Acta Crystallographica Section E, 2008)
The Zn atom in the title compound, [Zn(C7H5O3)2(C12H8N2)(H2O)]·H2O, exists in a distorted cis-ZnN2O4 octahedral coordination geometry. One of the 4-hydroxybenzoate anions chelates in a bidentate manner whereas the other is monodentate. The complex molecules are linked through the uncoordinated water molecules into a hydrogen-bonded sheet structure.